Food-Induced Hyperkinesis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The results of a controlled trial of hyposensitization with intradermal EPD (beta-glucuronidase and food antigens) in 40 children with the hyperkinetic syndrome are reported from the Universitatskinderklinik, Lindwurmstrasse, Munchen, Germany and The Allergy Unit, London, UK.